Alienation from school and cyberbullying among Chinese middle school students: A moderated mediation model involving self-esteem and emotional intelligence - Gan, Xiong; Wang, Pinyi; Huang, Chen; Li, Hao; Jin, Xin (Frontiers in Public Health, 2022)
As an extension of traditional bullying behavior, cyberbullying behavior emerges with the increasing popularity of the internet, and seriously affects the health of middle school students. However, just a few studies have explored the impact of the school factor on cyberbullying and its underlying mechanisms. Therefore, the purpose of this study is to explore the potential mediator (i.e., self-esteem) and potential moderator (i.e., emotional intelligence) of the relationships between alienation from school and cyberbullying. 575 Chinese middle school students participated in the study (45.74 % male) and completed self-report questionnaires regarding alienation from school, cyberbullying, self-esteem, and emotional intelligence. Correlation analysis showed a positive correlation between alienation from school and cyberbullying. Mediation analysis indicated that alienation from school positively predicts individual cyberbullying, and self-esteem partly mediated the association. Meanwhile, emotional intelligence moderated the pathway from alienation from school to cyberbullying. Specifically, the effect of high alienation from school on cyberbullying was weaker for middle school students who reported high emotional intelligence. The findings of this study expose the influence of the school factor and individual factors on cyberbullying, which has potential preventive and intervention value for youth cyberbullying.